COMPARATIVE STUDY OF ELECTROLYSIS-ENHANCED ANAEROBIC DIGESTION OF THREE SOLUBLE SOLID WASTES FOR BIOGAS PRODUCTION - Adewumi A; Lasisi K H; Akinmusere O K; Ojo A O; Babatola J O (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2020)
Aim: A comparative study of biogas production from three soluble solid wastes was conducted under anaerobic conditions by subjecting each waste to both conventional and electrolyzed digesters. Methodology and Results: Varying weight of each of the waste was mixed thoroughly with water and fed into five digesters. Three of these digesters were electrolytically-enhanced while the other two were not. The digestion of each of the wastes was monitored for 40 days at an ambient temperature ranging from 24 to 35oC. In all the digesters, biogas production started on the day 2, and attained maximum value on day 14 to17. Biogas production ended on the day 34 and 35 in digester 1a, 1b, 2a and 2b with production ending earliest in digester 3 containing wastewater on day 19. The highest biogas was produced in digester 2b containing electrolyzed digester loaded with poultry droppings) with a cumulative volume percentage of 91.41 as compared to its conventional state with a cumulative volume percentage of 85.19 and both states of the cow dung waste with cumulative volume percentages of 77.26 and 71.64 respectively. The least production occurred in digester 3 with a cumulative volume percentage of 4.59. Conclusion, significance and impact study: It is therefore concluded that poultry droppings has the greatest potentials for the generation of biogas as compared to cow dung in conventional and electrolyzed state and wastewater.